2022
DOI: 10.1007/s00227-021-04012-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific spatial segregation on a green turtle foraging ground in the Florida Keys, USA

Abstract: Assessing the distribution, density, and abundance of organisms is essential for conservation and management of imperiled species. Simple counts of sampled individuals are often inadequate to make such estimates. This is especially true for highly mobile marine animals like green sea turtles (Chelonia mydas). We used distance sampling and density surface model techniques to generate estimates of green turtle abundance on foraging grounds at the Eastern Quicksands, located west of Key West, Florida, USA. From 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Each transect was surveyed at approximately 15 km/hr during three non-consecutive survey days between the months of June and October in 2013. Transect and recording methods are described in Welsh and Mansfield [2] . We used two observers atop an elevated platform (eye-level = 4.5 m) on an 8.2 m survey vessel.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Each transect was surveyed at approximately 15 km/hr during three non-consecutive survey days between the months of June and October in 2013. Transect and recording methods are described in Welsh and Mansfield [2] . We used two observers atop an elevated platform (eye-level = 4.5 m) on an 8.2 m survey vessel.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…2005; Loṕez-Mendilaharsu et al, 2005;Welsh and Mansfield, 2022). Some authors suggested that size-specific vulnerability to sharks may be the root of this pattern, as they are the main natural predators of marine turtles and prefer to hunt them in shallows (Heithaus et al, 2006).…”
Section: Green Turtle Size Distributionmentioning
confidence: 99%
“…Juvenile animals, for example, can feed on sources not explored by adults or use habitats inaccessible to them, and vice versa (Werner and Gilliam, 1984;Ferreira et al, 2018). Intraspecific niche segregation is quite frequent among marine megafauna, and has been observed in most groups such as fish, birds, mammals, and reptiles (Breed et al, 2006;McClellan et al, 2010;Benjamins et al, 2015;Ferreira et al, 2018;de Lima et al, 2019;Louzao et al, 2019;Welsh and Mansfield, 2022).…”
Section: Introductionmentioning
confidence: 99%